2016
DOI: 10.3892/mco.2016.1012
|View full text |Cite
|
Sign up to set email alerts
|

ID1 upregulation and FoxO3a downregulation by Epstein-Barr virus-encoded LMP1 in Hodgkin's lymphoma

Abstract: Cancer-initiating cells (CICs) are specialized cells that have the ability to self-renew and are multipotent. We recently demonstrated that Forkhead box O3a (FoxO3a)-expressing cells exhibited a CIC-like potential in Hodgkin's lymphoma (HL). A proportion of HL patients are infected with Epstein-Barr virus (EBV). EBV-encoded latent membrane protein (LMP) 1 downregulates FoxO3a, suggesting that FoxO3a expression may be abolished in EBV-positive HL. Inhibitors of DNA-binding (ID) proteins are highly conserved tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Concerning the association between the two oncoviruses (EBV and HPV) and Id-1 gene, which is overexpressed in several human carcinomas, it has been reported that LMP1 onco-protein of EBV upregulates the expression of Id-1 but not FoxO3a in human Hodgkin’s lymphoma cells ( 31 ). Likewise, in nasopharyngeal carcinoma, LMP1 induces an upregulation of Id-1 via FoxO3a inactivation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the association between the two oncoviruses (EBV and HPV) and Id-1 gene, which is overexpressed in several human carcinomas, it has been reported that LMP1 onco-protein of EBV upregulates the expression of Id-1 but not FoxO3a in human Hodgkin’s lymphoma cells ( 31 ). Likewise, in nasopharyngeal carcinoma, LMP1 induces an upregulation of Id-1 via FoxO3a inactivation ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3a Downregulated FOXO3a expression, in result upregulating ID1 in Hodgkin's lymphoma (Ikeda et al, 2016)…”
Section: Lmp1mentioning
confidence: 99%
“…Concerning the association between the two oncoviruses (EBV and HPV) and Id-1 gene, which is overexpressed in several human carcinomas, it has been reported that LMP1 onco-protein of EBV up-regulates the expression of Id-1 but not FoxO3a in human Hodgkin's lymphoma cells 29 . Likewise, in nasopharyngeal carcinoma, LMP1 induces an upregulation of Id-1 via FoxO3a inactivation 30 .…”
Section: Discussionmentioning
confidence: 99%